Multi-exon deletions of the FBN1 gene in Marfan syndrome - Schrijver Iris; Liu Wanguo; Brenn Thomas; Furthmayr Heinz; Francke Uta (BMC, 2001)
Abstract Background Mutations in the fibrillin -1 gene (FBN1) cause Marfan syndrome (MFS), an autosomal dominant multi-system connective tissue disorder. The 200 different mutations reported in the 235 kb, 65 exon-containing gene include only one family with a genomic multi-exon deletion. Methods We used long-range RT-PCR for mutation detection and long-range genomic PCR and DNA sequencing for identification of deletion breakpoints, allele-specific transcript analyses to determine stability of the mutant RNA, and pulse-chase studies to quantitate fibrillin synthesis and extracellular matrix deposition in cultured fibroblasts. Southern blots of genomic DNA were probed with three overlapping fragments covering the FBN1 coding exons Results Two novel multi-exon FBN1 deletions were discovered. Identical nucleotide pentamers were found at or near the intronic breakpoints. In a Case with classic MFS, an in-frame deletion of exons 42 and 43 removed the C-terminal 24 amino acids of the 5th LTBP (8-cysteine) domain and the adjacent 25th calcium-binding EGF-like (6-cysteine) domain. The mutant mRNA was stable, but fibrillin synthesis and matrix deposition were significantly reduced. A Case with severe childhood-onset MFS has a de novo deletion of exons 44-46 that removed three EGF-like domains. Fibrillin protein synthesis was normal, but matrix deposition was strikingly reduced. No genomic rearrangements were detected by Southern analysis of 18 unrelated MFS samples negative for FBN1 mutation screening. Conclusions Two novel deletion cases expand knowledge of mutational mechanisms and genotype/phenotype correlations of fibrillinopathies. Deletions or mutations affecting an LTBP domain may result in unstable mutant protein cleavage products that interfere with microfibril assembly.